PEMAHAMAN KUANTITATIF DASAR DAN PENERAPANNYA DALAM MENGKAJI KETERKAITAN ANTARA BENTUK DAN MAKNA - Rajeg, Gede Primahadi Wijaya; Rajeg, I Made (Linguistik Indonesia, 2019)
This contribution discusses basic concepts of Chi-Square (χ2) test as a kind of analytical statistics and illustrates its application to one of the central issues in linguistics, namely form-meaning relationship. As a case study using Indonesian Web as Corpus from the Sketch Engine, this paper measures the association between morphosyntactic forms of words in the lexical field of panas ‘hot’ and their (non-)metaphorical usages. The χ2 test demonstrates a highly significant and robust association between the morphosyntactic form of words with the root panas ‘hot’ and their preference for (non-)metaphorical usages. The clear effects are shown by (i) the strong preference of the inchoative form memanas ‘to become hot’ for metaphorical usage, and (ii) the strong dispreference of dipanaskan ‘to be caused to be hot’ and panas ‘hot’ for metaphorical usage. This finding has implication on the predominant semantic trait of words with certain morphosyntactic forms, thus capturing the form-meaning relationship in language.